2017
DOI: 10.5004/dwt.2017.21430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyaniline maize tree-trunk composite on adsorption of lead (II) and cadmium (II) ions from solution

Abstract: a b s t r a c tHybrid nanostructured composite by polyaniline (PANi) and maize tree-trunk (MTT) was prepared by chemical polymerization method. Its structural morphology was nano range through SEM and TEM images. The decomposition temperature of PANi-MTT composite for 61.9% was about 341°C, less than that of PANi (about 507°C) for 46.6% through thermal analysis. It means this composite is less thermal stable than pure PANi because of MTT presence in composite matrix. The conductivity of PANi-MTT in salt form w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…for a 0.5 g•L -1 resin dose the time was 2 h against the more than the 5 h needed for the 0.065 g•L -1 resin dose. Experimental data were fit to the Freundlich and Langmuir models, the results from these fits indicated that the system responded better to the Freundlich mode (r 2 : 0.9074) (Babaei et al, 2017;Mai et al, 2017;Wang et al, 2017 (3)…”
Section: Lead Uptake Onto Amberlite Ir-120mentioning
confidence: 99%
“…for a 0.5 g•L -1 resin dose the time was 2 h against the more than the 5 h needed for the 0.065 g•L -1 resin dose. Experimental data were fit to the Freundlich and Langmuir models, the results from these fits indicated that the system responded better to the Freundlich mode (r 2 : 0.9074) (Babaei et al, 2017;Mai et al, 2017;Wang et al, 2017 (3)…”
Section: Lead Uptake Onto Amberlite Ir-120mentioning
confidence: 99%